Evidence for the relative age effect in the Spanish professional soccer league - Yagüe, J. M.; Molinero, O.; Alba, J. Á.; Redondo, J. C. (Journal of Human Kinetics, 2020)
The concept of the relative age effect refers to the consequences of the physical and psychological differences that may exist between those born earlier or later within the same calendar year. The objective of the present study was to examine this phenomenon in Spanish professional soccer, identifying the influences of the competitive level and the club of origin. The sample comprised 2,130 individuals from five competitive categories: under 12 (U12; n = 480), under 14 (U14; n = 338), under 16 (U16; n = 390), under 19 years old (U19; n = 489) and professional players (n = 433), with nine teams from the Spanish professional soccer league (PSL). Statistical analysis was based on a chi-squared test followed by calculation of the odds ratios and 95% confidence intervals. The main results show that at all levels of competition there was over-representation of individuals born in the first few months of the year. By clubs, the same over-representation was observed. It may be concluded that the relative age effect is consistent and exists throughout Spanish soccer, whether at youth or professional levels. An analysis by age categories showed a more pronounced effect in those competitions in which the youngest players participate, while in clubs the effect continued to be significantly present in all cases investigated in the study.